QUALITY OF SERVICE SUPPORT FRAMEWORK FOR HSP AIWIMAX INTEGRATED NETWORKS - OUSTA, FIRAS (2017)
Recently there has been much effort, in both academia and industry, to integrate a plethora of wireless technologies in order to provide ubiquitous broadband access to end-users. The vision of the Fourth Generation (4G) and beyond networks is an all-IP network, which also termed as Integrated Heterogeneous Networks (IHNs). IHNs includes diffurent service providers, multi-mode mobile terminals and diffurent types of access technologies such as High Speed Packet Access (HSPA), Long Term Evolution {LTE), Wireless Fidelity (Wi-Fi) and Worldwide Interoperability for Microwave Access (WiMAX).